Differences of fermentation performance of high-temperature Daqu in different production periods - CHEN Meimei, CHEN Fan, WEN Shangyu, MENG Tinglin, XIAO Zongyin, HUANG Xiaoping (Zhongguo niangzao)
The temperature, physicochemical indexes, microorganisms and tetramethylpyrazine during the fermentation process of high-temperature Daqu were monitored in different production periods (May, July, September, November 2023 and January 2024) in the hot and cold seasons (numbered ①, ②, ③, ④, ⑤, respectively, and the correlation between temperature, physicochemical indexes and tetramethylpyrazine was analyzed. The results showed that during the fermentation process, the temperature first increased and then decreased, the moisture and saccharification power decreased, the acidity increased, and the tetramethylpyrazine content increased first and then decreased, and fluctuated in a small range. At the end of fermentation, the moisture of Chucang high-temperature Daqu was 10%-12%. However, the saccharification power of high-temperature Daqu in the cold season (400-500 mg/(g·h) was higher than that of Daqu ①, ②, ③ (50-300 mg/(g·h)), the acidity (0.8-1.5 mmol/10 g) and tetramethylpyrazine contents (10-40 mg/kg) were lower than those of high-temperature Daqu in the hot season. Before the second turnover, some yeast and mold died, bacteria and Bacillus increased. After the second turnover, the mold increased. Before the second turnover, tetramethylpyrazine was positively correlated with temperature and negatively correlated with moisture. After the second turnover, tetramethylpyrazine was positively correlated with temperature, moisture and acidity, and negatively correlated with saccharification power.